FROM RITUAL TO REALITY:: The Application of Religious Values and Da'wah in Tahlilan in the Nahdliyin Community - Ramdani, Idan (Fakultas Dakwah dan Komunikasi UIN Sunan Kalijaga, 2023)
The tahlilan tradition in Sindangjaya Village is a religious practice rich in Islamic values, functioning as a medium for socialization and actualizing religious values. Not only does it function as a religious ritual to pray for people who have died, but also as an effective da'wah medium to spread Islam. This research aims to explore the role of tahlilan in cultivating religious values among the Nahdliyin community. Through interviews with religious leaders and local communities, it was found that tahlilan functions as a ritual to pray for people who have died and as a means to convey religious messages that include aspects of aqidah, worship, and morals. The process of socializing religious values in tahlilan involves two crucial aspects: the application of religious values in spiritual and social aspects. Tahlilan is a forum to strengthen people's relations with Allah (hablum minallah) and with fellow humans (hablum minannas). In addition, this tradition also serves as a tool to strengthen social solidarity and maintain good relations between citizens. The results of the study show that tahlilan has a significant impact on shaping the character and attitude of the community, as well as in internalizing religious values that are inherited from generation to generation. Thus, tahlilan is not only a religious ritual, but also an integral part of the cultural identity of the Nahdliyin people that needs to be preserved and developed.